Freshwater algae: functional properties and uses in the food industry - Vega Guevara, Keiko Lelyth (2025)
Freshwater algae are considered a very important resource within the food industry due to their high nutritional content and bioactive compounds. This review article aims to address microalgae and macroalgae as alternative/complementary protein sources and explore their potential applications in food products. The main types of freshwater microalgae (including cyanobacteria such as Arthrosporic and green algae such as Chlorella, Scenedesmus, and Haematococcus) are described, their morphology, ecological relevance, and applications (food, nutraceutical, and industrial). Likewise, the extraction and application methods of their components (conventional, ultrasonic, Soxhlet, microwave, CO2 (SFE) are detailed, comparing principles, operating parameters, yields, and benefits for the industry. The proximate and micronutrient composition of each algae (proteins, carbohydrates, lipids, ash, moisture, fiber, calcium, iron, and other minerals) is also presented, along with their current uses in functional foods (flours, beverages, baked goods). The use of omics technologies is incorporated as a tool to characterize algae and microalgae. Finally, the impacts of algae consumption on health, their contribution of amino acids and vitamins, and their antioxidant and anti-inflammatory properties, so highly sought after by consumers today when choosing a functional food, are discussed.